(untitled) (Alberta Journal of Educational Research, 2005)
This article explores how critical pedagogy and theatre arts can examine difference, change, and transformative possibilities in public spheres of educational practice. This narrative study offers a useful contribution on how theory, research, and practice can contribute to new ways of framing transformative feminist pedagogy in school cultures. I give an overview of critical pedagogy and the intersectionalities between concepts of liberatory pedagogy (Freire, 1970a) and the work of Brazilian theatre activist Augusto Boal (1979, 1992, 1995, 1998). I discuss how Boal’s philosophy and techniques of theatre of the oppressed can intersect in various ways with theatre arts curricula and feminist pedagogy. Using a case study of a young women’s theatre project Realtalk, I propose a postfeminist pedagogy and conditions for a form of radical education that offers a particular understanding of the complexities of how power is negotiated in schools across difference.